53c-23=23s

Simple and best practice solution for 53c-23=23s equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 53c-23=23s equation:


Simplifying
53c + -23 = 23s

Reorder the terms:
-23 + 53c = 23s

Solving
-23 + 53c = 23s

Solving for variable 'c'.

Move all terms containing c to the left, all other terms to the right.

Add '23' to each side of the equation.
-23 + 23 + 53c = 23 + 23s

Combine like terms: -23 + 23 = 0
0 + 53c = 23 + 23s
53c = 23 + 23s

Divide each side by '53'.
c = 0.4339622642 + 0.4339622642s

Simplifying
c = 0.4339622642 + 0.4339622642s

See similar equations:

| 4x=5+5x | | 6(4s+3)=114 | | 1+x+3=5 | | 18-x=6 | | 8(2l+4)=192 | | 1+3(5)= | | -252=6v+6(-6+5v) | | f(x)=0.5(4)x | | 4(8+3k)=116 | | x+(2x+4)=7 | | 5(x+2)=7(x) | | -4(3+4n)=-140 | | ln(4x^2-20x+24)= | | Solve(7x+2)2=64 | | 8*9=6x*12x | | (7-z)(5z-4)=0 | | -3+x-5((2x+4)-(x+2))=x+2 | | 14x^2-209x-15= | | 125=5(3v+7) | | b^2-4b-7=0 | | 10x-6=5x+10 | | e^4x=102.9 | | e(4x)=102.9 | | -4(1+8v)+3v=-178 | | 7(6-7x)=-105 | | 4x^2+5=x | | 4x^2-3x-9-(2x^2+22x+27)=0 | | 8(4x+8)-1=287 | | 2x^2-25x-36=0 | | 7(5-3n)=-112 | | x*3+10=11+x | | 7(1-5n)=182 |

Equations solver categories